2012
DOI: 10.1177/070674371205700708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of the Psychosis Phenotype

Abstract: Objective Relative to recent successes in elucidating the genetic mechanisms associated with complex diseases including macular degeneration, Type II diabetes, heart disease and cancer, molecular genetic approaches to psychiatric illness have met with more limited success. While factors such as small allelic effects, allelic heterogeneity and variation in population sub-structure have received considerable attention in attempt to explain the paucity of significant results in psychiatric genetics, significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Family history is considered one of the strongest risk factors for primary psychosis [16], with a heritability (i.e., the degree to which a phenotype, in this case a disorder, is genetically determined, calculated by regression-correlation analyses among close relatives) of schizophrenia estimated around 79-81% and a similar proportion in other disorders of the spectrum [17,18]. In particular, for close biologic relatives of patients with schizophrenia [13,19,20] was demonstrated a 7.5-fold higher risk for the development of primary psychosis [21] and studies on monozygotic twins [13,19,20] showed a concordance rate of approximately 50% [20,22].…”
Section: Individual Risk Factors Familiar and Parental Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Family history is considered one of the strongest risk factors for primary psychosis [16], with a heritability (i.e., the degree to which a phenotype, in this case a disorder, is genetically determined, calculated by regression-correlation analyses among close relatives) of schizophrenia estimated around 79-81% and a similar proportion in other disorders of the spectrum [17,18]. In particular, for close biologic relatives of patients with schizophrenia [13,19,20] was demonstrated a 7.5-fold higher risk for the development of primary psychosis [21] and studies on monozygotic twins [13,19,20] showed a concordance rate of approximately 50% [20,22].…”
Section: Individual Risk Factors Familiar and Parental Risk Factorsmentioning
confidence: 99%
“…The possible role of the product of gene loci associated with a higher risk of developing primary psychosis are described in Table 1 [17,18,22,42,43]. Genes were grouped according to the main function of their product.…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the process of asphyxia may also compromise other neural systems. Accordingly, we have previously found that expression of neuregulin 1 ( NRG1 ), a schizophrenia risk gene ( DeRosse et al, 2012 ), is significantly decreased in asphyxia-induced rats ( Wakuda et al, 2015 ). The protein encoded by NRG1 plays a role in regulation of synaptic plasticity and neurotransmission ( Mei and Xiong, 2008 ).…”
Section: Introductionmentioning
confidence: 99%